1980
DOI: 10.1097/00000658-198007000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Injuries Caused by Blunt Trauma

Abstract: Carotid artery injuries caused by blunt trauma often cause thrombosis and delayed neurologic deficits, and are associated with mortality rates of up to 40%. In this series of 17 patients with blunt trauma of the carotid, three had no symptoms, ten patients had limb paresis and four had severe neuroligic deficits. The wounds were identified by arteriography; repair was attempted in 15 patients, and successful in eight. All eight patients with successful repair were improved or normal after surgery, but only two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(46 citation statements)
references
References 13 publications
1
45
0
Order By: Relevance
“…The treatment of extracranial carotid artery dissection with anticoagulation has been proved to be effective, with an approximate 50%-70% arterial recanalization rate and a 10% risk of late neurologic deficits (32)(33)(34)(35)(36)(37)(38)(39). However, the high incidence of stroke within 30 days of the dissection (21%-41%) and the approximately 20% mortality rate make a compelling argument for alternative, more successful treatment strategies for overcoming these medical impasses (37).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of extracranial carotid artery dissection with anticoagulation has been proved to be effective, with an approximate 50%-70% arterial recanalization rate and a 10% risk of late neurologic deficits (32)(33)(34)(35)(36)(37)(38)(39). However, the high incidence of stroke within 30 days of the dissection (21%-41%) and the approximately 20% mortality rate make a compelling argument for alternative, more successful treatment strategies for overcoming these medical impasses (37).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] The patient's presenting symptom of cerebral ischemia may reveal the underlying cerebrovascular injury. Carotid artery injuries generally result in contralateral sensorimotor deficits, while VAIs typically manifest as ataxia, dizziness, vomiting, facial or body analgesia, or visual field defects.…”
Section: Historical Perspectivementioning
confidence: 99%
“…12 The most common mechanism causing CAI is hyperextension resulting from the stretching of the carotid artery over the lateral articular processes of C1-C3. [13][14][15][16][17][18] Vertebral artery injuries are likely a combination of direct injury, due to associated fractures of the vertebrae involving the transverse foramen through which the artery courses, and hyperextension-stretch injury due to the tethering of the vertebral artery within the lateral masses of the cervical spine. Regardless of mechanism, there is intimal disruption of the carotid or vertebral artery.…”
Section: Historical Perspectivementioning
confidence: 99%
“…In case of injury in zone II the laceration site is confirmed through neck exploration (10). Kim et al (3) confirmed the priority of endovascular treatment for carotid artery injury; however endovascular procedure was not able due to full transaction of CCA.…”
Section: Discussionmentioning
confidence: 99%